Maresin 1 Inhibits Epithelial-to-Mesenchymal Transition in Vitro and Attenuates Bleomycin Induced Lung Fibrosis in Vivo. Issue 5 (November 2015) - Wang, Yaxin; Li, Ruidong; Chen, Lin; Tan, Wen; Sun, Zhipeng; Xia, Haifa; Li, Bo; Yu, Yuan; Gong, Jie; Tang, Min; Ji, Yudong; Yuan, Shiying; et al.
Abstract : ABSTRACT: Lung fibrosis is an aggressive disease with uncontrolled fibrotic response and no effective therapeutic treatment. Epithelial-to-mesenchymal transition (EMT) has been proved to be an important pathological feature in lung fibrosis. In this study, we investigated whether MaR1, a kind of proresolving lipid mediators, could inhibit TGF-β1-induced EMT in vitro and lung fibrosis in vivo. In vitro study, mouse type II alveolar epithelial cells were treated with different does of MaR1 for 30 min and were exposed to TGF-β1 for 48 h. In vivo study, C57BL/6 mice were administered bleomycin intratracheally. After 14 days, MaR1 was injected intraperitoneally daily for 7 days. In day 28, mice were sacrificed. The results demonstrate that treatment of mouse type II alveolar epithelial cells with MaR1 (10 nM) significantly prevents TGF-β1-induced fibronectin and α-SMA expression and restores E-Cadherin level. The down-regulation of profibrotic molecules of MaR1 is associated with suppression of Smad2/3 and Akt phosphorylation. In vivo, MaR1 treatment significantly prolongs survival rate and attenuates destruction of lung architecture, as well as collagen deposition after bleomycin inhalation. TGF-β1 concentration in bronchoalveolar lavage and fibrotic markers (fibronectin and α-SMA) in lung tissues are inhibited by MaR1 administration. These data indicate that MaR1 inhibits TGF-β1-induced EMT and attenuates bleomycin-induced pulmonary fibrosis. MaR1 may be a promising strategy for alleviation of lung fibrosis.